Vaccination Policy Problems in the Implementation of Social Restrictions due to Covid-19 - Al Kariem, Emilio Idi (Universitas Syiah Kuala, 2023)
This study discusses the problem of the vaccination program as one of the measures to prevent the spread of Covid-19. The purpose of this study is to analyze why this vaccination policy problem arises by using analysis and implementation models in public policy theory. This research uses qualitative research methods with literature studies which are then strengthened by data and facts that occur through observation by looking at the symptoms that occur which are then analyzed using simplified data reduction methods to find the latest facts of a problem that arises. This policy causes problems, especially in Indonesia. This policy causes rejection because this policy is an obligation people are forced to follow if they do not want their daily activities to be restricted so it has the potential to violate human rights and a sense of justice, in addition that many people doubt the success of the vaccine itself and the side effects that will occur to the body, And also because this policy often changes and makes people feel unsafe. After all, it has the potential to violate privacy so that it will affect the target of the vaccination program that has been set by the government due to reactions from the public.